“Hoarding” a Menace to the Socio-Economic Development of Nigeria: Panacea in the Light of Selected Ahādīth in Ṣunan Ibn Mājah - Abdul-Rahman, Babatunde Yunus; Daud Olalekan, Abdulsalam; Saheed Adewale, Badmus (Al-Basirah Journal, 2025)
Hoarding (iḥtikār) has become a major contributor to Nigeria’s socio-economic instability, leading to artificial scarcity, rising prices, and the exploitation of vulnerable citizens. This study examines the phenomenon of hoarding in contemporary Nigeria through the lens of selected ahādīth from Sunan Ibn Mājah, with the aim of identifying Islamic ethical responses that may serve as effective remedies. Adopting historical, analytical, and phenomenological methods, the study outlines the juristic definitions of hoarding, assesses its economic effects, and analyses relevant prophetic teachings that condemn unethical market practices. The paper reveals that hoarding contributes significantly to inflation, wealth concentration, market distortion, and various social vices. It also reveals that hoarding contributes significantly to inflation, wealth concentration, market distortion, and various social vices. It is also reveals that the meaning of hoarding extends beyond physical commodities to include knowledge, money, and essential social resources. It concludes that Islamic teachings offer holistic and practical solutions that can guide policy makers and religious educators in curbing hoarding and mitigating its effects on the Nigerian economy.